2019
DOI: 10.21608/eajbsc.2019.71752
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Annona muricata (Graviola) and Fullerene C60 Against Toxicity Induced by Carboplatin in Male Albino Rats

Abstract: This study was designed to demonstrate the ameliorating effects Annona muricata (Graviola) plant extract and fullerene C 60 on hematological and biochemical disorder alteration induced by intraperitoneal (i.p.) injection of carboplatin (CRP) on male rats. Five groups of adult male rats we established (n=10). Group1: animals were administered normal saline i.p. (10 ml/kg b.wt) for 40 days and served as a normal group. Group 2: rats were injected i.p. with a single dose of CRP (80 mg/kg b.wt), then received a sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…High level of serum alkaline phosphatase is related to synthesis increased of it by cells lining bile canaliculi usually in response to cholestasis and increased biliary pressure (Kanchana andSadiq, 2011 andKasem, 2019). In addition, Senthilkumar et al (2006) found that hypo-proteinemia was observed in rats injected with CP for two days and attributed to the CP exerts a direct impact on plasma cells where, it inhibits protein synthesis and results in a liver damage cells.…”
Section: Discussionmentioning
confidence: 99%
“…High level of serum alkaline phosphatase is related to synthesis increased of it by cells lining bile canaliculi usually in response to cholestasis and increased biliary pressure (Kanchana andSadiq, 2011 andKasem, 2019). In addition, Senthilkumar et al (2006) found that hypo-proteinemia was observed in rats injected with CP for two days and attributed to the CP exerts a direct impact on plasma cells where, it inhibits protein synthesis and results in a liver damage cells.…”
Section: Discussionmentioning
confidence: 99%